Word-formation in second language acquisition - Cornelia Tschichold (Word-formation: an international handbook of the language of Europe, 2015)
This article explores the role of word-formation processes in the acquisition of a second-language lexicon and the relevant concepts from second language acquisition theory, among them the ‘word family’. The acquisition of word-formation knowledge influences the structure of a speaker’s mental lexicon, but teaching word-formation explicitly is sometimes seen as an optional extension for advanced learners. Dictionaries can help learners develop their knowledge of word-formation, but only electronic versions can make full use of the lexical information.